What drives the productive efficiency of a firm? The importance of industry, location, R&D, and size - Oleg Badunenko; Michael Fritsch; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper investigates the factors that explain the level and dynamics of manufacturing firm productive efficiency. In our empirical analysis, we use a unique sample of about 39,000 firms in 256 industries from the German Cost Structure Census over the years 1992-2005. We estimate the efficiencies of the firms and relate them to firm-specific and environmental factors. We find that (1) about half the model's explanatory power is due to industry effects, (2) firm size accounts for another 20 percent, and (3) location of headquarters explains approximately 15 percent. Interestingly, most other firm characteristics, such as R&D intensity, outsourcing activities, or the number of owners, have extremely little explanatory power. Surprisingly, our findings suggest that higher R&D intensity is associated with being less efficient, though higher R&D spending increases a firm's efficiency over time.
Keywords: D24; L10; L25; 330; Frontier analysis; determinants of efficiency; firm performance; industry effects; regional effects; firm size; Verarbeitendes Gewerbe; Produktivität; Technische Effizienz; Kostenstruktur; Branche; Standort; Betriebsgröße; Industrielle Forschung; Deutschland